Respuesta :
Hey!
So if you mean find h(-8), then you would just plug in -8 for t!
-2(-8+5)^2 + 4 = h(t)
Don't forget about PEMDAS!
So first we are going to solve the parenthesis.
-2(-3)^2 + 4 = h(t)
now the exponent
-2(9) + 4 = h(t)
you might be wonder why it's 9 and not -9, that is because since the -3 is in parenthesis, the - is included and -3 times -3 is 9. If the - was not included in the parenthesis and was on the outside then it would be -9.
Let's carry on.
Now multiply
-18 + 4 = h(t)
Now add and get your answer
-14 = h(8)
Your answer is -14!
Hope this helps!
So if you mean find h(-8), then you would just plug in -8 for t!
-2(-8+5)^2 + 4 = h(t)
Don't forget about PEMDAS!
So first we are going to solve the parenthesis.
-2(-3)^2 + 4 = h(t)
now the exponent
-2(9) + 4 = h(t)
you might be wonder why it's 9 and not -9, that is because since the -3 is in parenthesis, the - is included and -3 times -3 is 9. If the - was not included in the parenthesis and was on the outside then it would be -9.
Let's carry on.
Now multiply
-18 + 4 = h(t)
Now add and get your answer
-14 = h(8)
Your answer is -14!
Hope this helps!